The Effectiveness of Canva Media Using the Process Skills Approach in Learning Speech Text Writing Skills - Arifah, Dinil; Charlina (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to test the effectiveness of Canva media in teaching speech text writing skills using a process skills approach in class VIII MTs Pondok Pesantren Baituddin Petapahan. The background of this study is the low learning outcomes of students, which are caused by the dominance of conventional methods and the lack of visualization of materials in learning Indonesian. The study employed a quantitative approach with a quasi-experimental design involving two groups: the experimental group and the control group. The study population consisted of 32 students. The sample was set at 30 student. The research instrument was an essay test administered before and after the application of Canva media. A checklist was used to validate the scoring results and internal data analysis. Data on learning outcomes of speech text material for both pretest and posttest were analyzed using parametric inferential statistical procedures. The appropriate procedure for this is a one-sample t-test for pretest and posttest data and a paired sample t-test for comparative data between posttest and pretest results preceded by an assumption test. The results of the study: 1) the pretest for speech text writing skills for both research groups was relatively low; 2) the procedure for learning the skills of writing speech texts using the process skills approach in Canva media; 3) the posttest of the skills of writing speech texts for the experimental group in learning using Canva media is higher than the learning outcome group in the control using conventional media. Thus, the synthesis of this study is that Canva media is effective for use in learning speech material in class VIII.